A fully Lagrangian method for fluid–structure interaction problems with deformable floating structure. (October 2019) - Sun, Yijie; Xi, Guang; Sun, Zhongguo
Abstract: A fully Lagrangian meshless method was developed to solve the nonlinear fluid–structure interaction (FSI) problem. The improved moving particle semi-implicit (MPS) method was applied to simulate the incompressible fluid flow, and the bonded-particle model (BPM) was introduced in the discrete element method (DEM) to predict the structure deformation. The coupled MPS–DEM method was established based on the refined interface force calculation and time steps matching. In addition, a new dimensionless parameter, the deformation coefficient (DC), was proposed to quantitatively evaluate the deformation and displacement changes for the deformable structure. The oscillation of the DC would show the position fluctuation on the structure due to the deformation, and it makes the stability analysis of the deformable structure more comprehensive and reasonable. The proposed MPS–DEM(BPM) method was developed to study the motion of the moored deformable structure under solidary wave, and the effect of the Young's modulus on the stability of the deformable structure was discussed.